Prolonged Inhalation Exposure to Coal Dust on Irradiated Rats and Consequences - Laura Chulenbayeva; Oralbek Ilderbayev; Dametken Suleymeneva; Aizhan Kaliyeva; Symbat Kabdykanov; Madiyar Nurgaziyev; Ayaulym Nurgozhina; Shynggys Sergazy; Samat Kozhakhmetov; Almagul Kushugulova (The Scientific World Journal)
The purposes of this study were to research immune system changes and liver and lung tissues in irradiated rats after prolonged exposure to coal dust. A study was carried out on 30 male Wistar rats that were divided into 3 groups: group I, intact animals; group II, exposure to coal dust and 0.2 Gy γ-irradiation; and group III, combined exposure to 6 Gy γ-irradiation and coal dust. The combination of a low and sublethal dose of γ-irradiation with coal dust leads to a significant change in immunity at the remote period. Particularly, the increase in radioactivity at the combined effect causes weakening of phagocytosis, and reduction in T lymphocytes by a factor of 2, immunoglobulin imbalance, and cytokine dysfunction develop secondary immune failure. During prolonged inhalation with coal dust of irradiated animals with the dose of 0.2 Gy, fibrosis and perivascular sclerosis of the bronchial wall of the lungs are formed, and perivascular fibrosis is formed in the liver. The increase in exposure dose up to 6 Gy in combination with coal, in the distant period, caused pulmonary hypertension amid hypertrophy of light arterial vessels and fibrous changes in arteriole, and destructive changes and collection necrosis develop in liver parenchyma. In the case of dust radiation synergy, the increase in doses leads to a significant immune deficiency, which occurs according to the “dose effect” principle; increases damage to animal tissues; and leads to liver tissue necrosis, pulmonary fibrosis, and pulmonary hypertension.